Investigação da base molecular e história evolutiva do melanismo em felídeos selvagens - Schneider, Alexsandra (2013)
Melanism is a very common coat color polymorphism in felids, and has been defined as an increased production of dark melanin which generates a general darkening of the organism s tegument. Such coloration variation in mammals is often be regulated by the action of two genes and their products: MC1R and ASIP. Eumelanin (dark pigment) is produced when the Melanocortin-1 receptor (MC1R) is activated by the binding of the Alpha Melanocyte Stimulating Hormone (α-MSH). In contrast, MC1R activation is inhibited by the binding of the antagonist peptide ASIP (Agouti Signaling Protein), whose action leads to a switch to pheomelanin (light pigment) synthesis. Melanism has been documented in 13 out of 37 extant felid species, in some cases reaching high frequencies at the population level. A previous studies has indicated that this phenotype arose multiples times in the Felidae, with three different species exhibiting unique mutations associated with this trait (EIZIRIK et al., 2003). In this context, the present study aimed to identify the mutations implicated in this phenotype in five other felid species, and to investigate in more detail the evolutionary dynamics of melanism in the Felidae. In the first article, we revealed two additional cases of species-specific mutations involved in melanism in Asian wild cats, Panthera pardus and Pardofelis temminckii, and discuss the role of the ASIP gene in the evolution of this mutant phenotype. In the second manuscript, we analyzed the evolution of melanism in an endemic lineage of Neotropical felids belonging to the genus Leopardus. This lineage includes three species of small wild cats that were the focus of this study: L. colocolo, L. guigna e L. geoffroyi. The presence of melanism in these closely-related species, along with relatively high frequencies (ranging from 20% to 30%) of this phenotype observed in some areas of their geographic distribution, suggests that natural selection may be involved in the origin and evolution of this trait. In this context, we identified three novel mutations in the ASIP and MC1R genes, each of them strongly associated with melanism in one of the analyzed species, and revealed that natural selection may have played a role in the evolutionary history of melanism in this lineage of felids.